Interrelationship of Repair Mechanisms in Ultraviolet-Irradiated Escherichia coli - Moss, S. H. (1974)
Investigation of the effect of photoreactivation, excision, and recombination repair, individually and in combination, on the survival of ultraviolet-irradiated Escherichia coli K-12 mutants has led to a possible explanation of the loss of photoreactivability and of the complex changes in viability observed during liquid-holding. It is suggested that at higher ultraviolet light doses the excision repair mechanism becomes saturated due to overlapping of excised regions on opposite strands of the deoxyribonucleic acid helix. The results also provide support for the existing hypothesis that states that the shape of shouldered survival curves of ultraviolet-irradiated bacteria can be described in terms of the probability of occurrance of overlapping excised regions. Using the data obtained with repair-deficient mutants with closely related genetic makeup, we present a mathematical model that accurately predicts the shape of the observed survival curves and provides an estimate of the number of nucleotides in each fragment of deoxyribonucleic acid removed by the excision repair mechanism.